Bacteriophages: A possible solution to combat enteropathogenic Escherichia coli infections in neonatal goats. (1st May 2022) - Bhargava, K.; Gururaj, K.; Aseri, G. K.; Nath, G.; Singh, N. P.; Pawaiya, R. V. S.; Kumar, A.; Mishra, A. K.; Yadav, V. B.; Jain, N.
Abstract: Due to awareness and benefits of goat rearing in developing economies, goats' significance is increasing. Unfortunately, these ruminants are threatened via multiple bacterial pathogens such as enteropathogenic Escherichia coli (EPEC). In goat kids and lambs, EPEC causes gastrointestinal disease leading to substantial economic losses for farmers and may also pose a threat to public health via the spread of zoonotic diseases. Management of infection is primarily based on antibiotics, but the need for new therapeutic measures as an alternative to antibiotics is becoming vital because of the advent of antimicrobial resistance (AMR). The prevalence of EPEC was established using bfpA gene, uspA gene and Stx1 gene, followed by phylogenetic analysis using Stx1 gene. The lytic activity of the isolated putative coliphages was tested on multi‐drug resistant strains of EPEC. It was observed that a PCR based approach is more effective and rapid as compared to phenotypic tests of Escherichia coli virulence. It was also established that the isolated bacteriophages exhibited potent antibacterial efficacy in vitro, with some of the isolates (16%) detected as T4 and T4‐like phages based on gp23 gene. Hence, bacteriophages as therapeutic agents may be explored as an alternative to antibiotics in managing public, livestock and environmental health in this era of AMR. Abstract: Significance and Impact of the Study: Ruminants are susceptible to various bacterial infections, which are treated with antibiotics that are increasingly failing due to AMR. Hence bacteriophages can be employed to treat such bacterial infections. Due to rising AMR the interest in phage therapy has recently been renewed, although its application in veterinary medicine remains a long way off. This research focused on the management of enteropathogenic E. coli (EPEC) through optimal PCR‐based detection strategy and the use of bacteriophages as a therapeutic alternative to antibiotics to combat EPEC infections in neonatal goats.